Student perceptions of older adults after a music intervention: A mixed approach. (May 2021) - Emory, Jan; Bowling, Hilary; Lueders, Cynthia
Abstract: Aims: The aims of this project were to investigate changes in nursing students' attitudes and perceptions of older adults after implementing individualized Music and Memory© playlists. In addition, the inquiry sought to compare pre and post survey responses for changes in rankings of caring for the older adult as a career choice. The qualitative inquiry sought to explore students' perceptions of their experience through narrative journaling for a better understanding of the experience. Design: This study used an explanatory sequential mixed design. Methods: A pre post-intervention approach was used for quantitative data collection along with a ranking item for career choices. Journal narratives completed within one week following the experience were explored for qualitative themes to better understand students' experiences. Attitudes and perceptions of students ( N = 44) were measured by two tools before and after implementation of Music and Memory© Interventions during a 7-week clinical experience. Student journals were analyzed for themes. Results: In the two-tailed paired t -test, nursing students' attitudes and perceptions of caring for older adults were analyzed for differences. Significance improvement was found in students' reported interaction scores and other constructs ( p ≤ .01). Mean ranking of caring for the older adult improved from 7.6 to 7.0 in the post intervention analysis. Student journals reported the activity as worthwhile and time consuming. Conclusions: As the baby boomer generation ages the need for residential long-term care is projected to increase significantly. Recruiting and retaining nurses to care for this vulnerable population is challenging. Music and Memory© Interventions have the potential to change student attitudes and perceptions of the older adult that could improve caring for the older adult as a career choice. Highlights: Nursing students' attitudes and perceptions of older adults effect career choices. Music and Memory© Interventions promote improved attitudes and perceptions. Nurse educators should integrating authentic learning strategies into curricula.